Evolusi Bentuklahan daerah Manado dan sekitarnya, Sulawesi Utara - S. Poedjoprajitno (Geological Agency, 2009)
http://dx.doi.org/10.17014/ijog.vol4no2.20096Landform evolusion in Manado region has been strongly influenced by tectonic activities beside marine and volcanic ones. Based on surface and subsurface (shallow drilling) geological data, landform evolution of the studied areas can be grouped into four morphological environment units consisting of nine environment sets of morphology, these are: ( a). flood basin, ( b). tidal beach, (c).swamp, (d). river channel, (e).volcanic eruption, (f). flood basin influenced by water, (g).coastal/shore, (h). near shore, and (i). offshore. Collumnar analyses on nine drilling data show that the landform evolution history in the Manado region has undergone more than one tectonic event and three eruptions, proved by the presence of discontinuities on morphological environment units and composition, vertically.